Anterior patterning genes induced by Zic1 are sensitive to retinoic acid and its metabolite, 4‐oxo‐RA. Issue 3 (24th September 2021) - Dubey, Aditi; Saint‐Jeannet, Jean‐Pierre
Abstract: Background: Development of paired sensory organs is a highly complex and coordinated process. These organs arise from ectodermal thickenings in the cephalic region known as cranial placodes. We have previously shown that Zic1 is a critical regulator for the formation of the pre‐placodal region (PPR), the common territory for the development of all cranial placodes in Xenopus laevis . Results: In this study, we have analyzed a number of Zic1 targets for their expression during PPR patterning, as well as their regulation by retinoic acid (RA) and one of its major metabolites, 4‐oxo‐RA. Our findings show that anteriorly Zic1 regulates several transcription factors, Crx, Fezf2, Nkx3‐1, and Xanf1 as well as a serine/threonine/tyrosine kinase, Pkdcc.2. These factors are all expressed in the vicinity of the PPR and as such are candidate regulators of placode formation downstream of Zic1. In addition to their differential regulation by RA, we find that 4‐oxo‐RA is also capable of modulating the expression of these genes, as well as a broad array of RA‐regulated genes. Conclusion: Our data highlight the complexity of retinoid‐mediated regulation required for Zic1‐activated anterior structure specification in Xenopus, and the potential physiological role of 4‐oxo‐RA in cranial placode development. Key Findings: Crx, Fezf2, Nkx3‐1, Xanf1 and Pkdcc.2 are novel Zic1 targets during cranial placode formation. Their expression is regulated by retinoic acid (RA) and one of its major metabolites, 4‐oxo‐RA. Global analysis indicates that 4‐oxo‐RA is capable of regulating gene expression in a manner similar to RA. We propose that 4‐oxo‐RA acts as an active morphogen during cranial placode development.